THE EFFECT OF WORKLOAD AND AUDITOR SPECIALIZATION ON AUDIT QUALITY WITH AUDIT COMMITTEE QUALITY AS MODERATING VARIABLE - Erma Setiawati; Eskasari Putri; Dyana Madyaratri (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhammadiyah Palopo, 2021)
ABSTRAKÂ The study aims to axamine the effect of workload and specialization of auditors on audit quality with quality of the audit committee as a moderating variable. This research is a quantitative study using a descriptive approach. The population in this research is a Jakarta Islamic Index (JII) companies listed on the Sharia Exchange in 2016-2018. The sampling technique in this study used the purposive sampling method. Data analysis method used was logistic regression analysis method using Statistical Package for Social Sciences (SPSS) version 21 program. The result of this research indicate that workload give impact on audit quality. Specialization of auditors, and quality of the audit committee do not impact on audit quality. Moderating analysis shows that quality of the audit committee is not able to moderate workload and specialization of auditors on audit quality.Kata Kunci:Â Â audit quality, workload, auditor spe-cialization, audit committee